Variables For the Diagnostic Fase of a Pilot Software of Strategic Planning - Sánchez-Riaño, Vladimir; Suarez Baez, Liliana C.; Garcia-Bedoya, Olmer; Sojo-Gomez, Jairo R. (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This article is a research result of the Strategic Planning Semiotic Model Project, financed by Jorge Tadeo Lozano University. The project seeks to establish variables for the diagnostic phase of a pilot Software that supports the processes of strategic advertising planning. The starting point was the analysis of the real cases with the Effie College Colombia 2018 and 2019 awards, especially the cases in which the research group obtained two gold awards. These cases let to establish requirements over the diagnostic phase for profiling the client's situation and brand context from four categories: markets, communication, people, and trends.